Strategies for Improving Contextual Performance in Government Employees: Analyzing Effects of Servant Leadership, Person-Environment Fit, and Emotional Intelligence - Prastiwi; Amiartuti Kusmaningtyas; I Dewa Ketut Raka Ardiana (Journal of International Business, Economics and Entrepreneurship, 2024)
Contextual performance refers to employee contributions and primary duties. These include support, initiative, and active participation. This study discusses the effect of servant leadership and person-environment fit on improving employee contextual performance through emotional intelligence in government. 124 employees were research samples based on purposive sampling. This research uses Structural Equation equation model (SEM) with quantitative methods. The results stated that servant leadership is significant on emotional intelligence, person environment is significant on emotional intelligence, servant leadership is insignificant on contextual performance, person environment is significant on contextual performance, and emotional intelligence is significant on contextual performance. This indicates that emotional intelligence has an important role in improving employees' contextual performance, while servant leadership does not directly affect contextual performance. The implication of this research is the importance of developing emotional intelligence and person-environment fit in government organizations to improve employee performance.